Allergological Importance of Invertebrate Glutathione Transferases in Tropical Environments - Zakzuk, Josefina; Lozano, Ana; Caraballo, Luis (Frontiers in Allergy, 2021)
Glutathione transferases (GST) comprise a ubiquitous family of dimeric proteins that participate in detoxification reactions. It has been demonstrated that various GSTs induce allergic reactions in humans, being those from house dust mites (HDM), cockroaches and helminths the best characterized. Evaluation of their allergenic activity suggests they have clinical impact. GST allergens belong to different classes: mu (Blo t 8, Der p 8, Der f 8 and Tyr p 8), sigma (Bla g 5 and Asc s 13), or delta (Per a 5) GST class. Also, IgE binding molecules belonging to the pi-class have been discovered in helminths, but they are not officially recognized as allergens. In this review, we describe some aspects of the biology of GST, analyze their allergenic activity and explore the structural reasons and clinical impact of their cross-reactivity.